Increasing surfboard volume reduces energy expenditure during paddling - Ekmecic, V.; Jia, N.; Cleveland, T. G.; Saulino, M.; Nessler, J. A.; Crocker, G. H.; Newcomer, S. C. (Ergonomics, 2017)
The purpose of this study was to investigate how altering surfboard volume (BV) affects energy expenditure during paddling. Twenty surfers paddled in a swim flume on five surfboards in random order twice. All surfboards varied only in thickness and ranged in BV from 28.4 to 37.4 L. Measurements of heart rate (HR), oxygen consumption (VO2), pitch angle, roll angle and paddling cadence were measured. VO2 and HR significantly decreased on thicker boards [VO2: r = -0.984, p = 0.003; HR: r = -0.972, p = 0.006]. There was also a significant decrease in pitch and roll angles on thicker boards [Pitch: r = -0.995, p < 0.001; Roll: r = -0.911, p = 0.031]. Results from this study suggest that increasing BV reduces the metabolic cost of paddling as a result of lower pitch and roll angles, thus providing mechanical evidence for increased paddling efficiency on surfboards with more volume.